Maternal plasma proteomics in a rat model of pregnancy complications reveals immune and pro‐coagulant gene pathway activation. (23rd November 2019) - Sanchez, Tino W.; Li, Bo; Molinaro, Christine; Casiano, Carlos A.; Bellinger, Denise L.; Mata‐Greenwood, Eugenia
Abstract: Problem: The Brown Norway (BN) rat is a model of T‐helper 2 immune diseases, and also a model of pregnancy disorders that include placental insufficiency, fetal loss, and pre‐eclampsia‐like symptoms. The aim of this study was to investigate the plasma proteomic/cytokine profile of pregnant BN rats in comparison to that of the Lewis (LEW) rat strain. Method of study: Plasma proteomics differences were studied at day 13 of pregnancy in pooled plasma samples by differential in‐gel electrophoresis, and protein identification was performed by mass spectrometry. Key protein findings and predicted cytokine differences were validated by ELISA using plasma from rats at various pregnancy stages. Proteomics data were used for ingenuity pathway analysis (IPA). Results: In‐gel analysis revealed 74 proteins with differential expression between BN and LEW pregnant dams. ELISA studies confirmed increased maternal plasma levels of complement 4, prothrombin, and C‐reactive protein in BN compared to LEW pregnancies. LEW pregnancies showed higher maternal plasma levels of transthyretin and haptoglobin than BN pregnancies. Ingenuity pathway analysis revealed that BN pregnancies are characterized by activation of pro‐coagulant, reactive oxygen species, and immune‐mediated chronic inflammation pathways, and suggested increased interleukin 6 and decreased transforming growth factor‐β1 as potential upstream events. Plasma cytokine analysis revealed that pregnant BN dams have a switch from anti‐ to pro‐inflammatory cytokines with the opposite switch observed in pregnant LEW dams. Conclusion: Brown Norway rats show a maternal pro‐inflammatory response to pregnancy that likely contributes to the reproductive outcomes observed in this rat strain.